Kontribusi Ekxplosive Power Otot Tungkai Dan Keseimbangan Terhadap Kemampuan Tendangan Sabit Pada Pesilat Di Perguruan Kemenyan Putih Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak - Ariansyaha, Sirka; Rezki, Rezki (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to determine the contribution of explosive power of leg muscles and balance to the ability of sickle kicks in fighters at Perguruan Kemenyan Putih Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak. This type of research is correlation. The population in this study was 18 male martial artists at the Perguruan Kemenyan Putih Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak. The sampling technique used was total sampling so that the sample in this study was 18 people. The research instruments used were the standing brodjump test, stork stand test and sickle kick ability test. The data analysis technique used is the multiple correlation value test and calculating the contribution value. (1) There is a contribution of explosive leg muscle power to the sickle kick ability of fighters at the Perguruan Kemenyan Putih Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak with a value of rcount = 0.670 > rtable = 0.468 and a KD value of 44.89%, (2) There is a balance contribution to kicking ability sickle fighter at the Perguruan Kemenyan Putih Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak with a value of rcount = 0.552 > rtable = 0.468 and a KD value of 30.47%. (3) There is a contribution of explosive leg muscle power and balance to the crescent kick ability of fighters at the Perguruan Kemenyan Putih Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak with a value of rcount = 0.723 > rtable = 0.468 and a KD value of 52.27%.